Rabbi Yitzchak Hutner's Theology of Meaning : The World Was Created for Me" Studies in Musar Series, Volume 2" - Shalev, Alon (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025, 2025)
Rabbi Yitzchak Hutner's Theology of Meaning explores the profound, enigmatic, and novel thought of Rabbi Yitzchak Hutner, combining innovative analysis with rigorous textual and historical research. Through a reconstruction of his intellectual biography and the conceptual framework underlying his ideas, this volume generates a hermeneutical key to decipher his writings, revealing their focal points and systematic coherence, and positioning him as a post-existentialist theologian bridging Jewish tradition, modern philosophy, and existential inquiry. The methodology presented offers a valuable model for analyzing complex intellectual systems, making it essential reading for scholars of philosophy, theology, and intellectual history.